The first report of an Eastern Great Tit Parus minor nestling’s foot entanglement with human hairs at Hongneung Experimental Forests in Seoul - Kim, Eun-Jeong; Seo, Hae-min; Oh, Jeong-Hak; Park, Chan-Ryul (The Korean Journal of Ornithology, 2020)
Few cases have been recorded of the entanglement effects of anthropogenic materials on the breeding ecology of forest birds, though urbanization affects the breeding status of birds in urban forests. To understand the use of anthropogenic nesting materials, we recorded the breeding performance of the Eastern Great Tit (Parus minor) in installed artificial nest boxes at Hongneung Experimental Forests in Seoul. We observed one nestling damaged by human hairs from 12 to 25 May 2020 and recorded the damage effects of human hairs on the breeding of the Eastern Great Tit in Hongneung Experimental Forests. KCI Citation Count: 1